Postoperative systemic arterial hypertension in infants with congenital heart diseases: prevalence and risk factors - Xiaohong Chen; Yanling Chen; Lijie Zhao; Ruikun Zou; Yuan Ren; Xin Sun; Xinmeng Zhang; Haiyun Yuan; Yifei Wang (Blood Pressure)
Objective To determine the prevalence rate and risk factors for systemic arterial hypertension in infants with congenital heart diseases.Methods A retrospective cohort study of postoperative systemic arterial hypertension incidence in infants who underwent cardiac surgery was conducted. The primary diagnosis was retrieved. The general characteristics, surgical information, and blood pressure data at five periods were also collected. The five periods were at admission, 48 hours after cardiac surgery (postoperative), at discharge, at full-time, and at any time during hospitalisation. The risk factors for postoperative hypertension and hypertension at discharge were determined by multivariate logistic regression.Results This study enrolled 1205 eligible infants. The age and weight at surgery were 27.0 (13.0, 59.0) days and 3.53 ± 0.96 kg, respectively. The prevalence rates of postoperative hypertension and hypertension at discharge were 12.8 (10.9–14.7)% and 6.9 (5.5–8.3)%, respectively. The incidence of postoperative hypertension varies greatly across different types of congenital heart diseases. A low weight Z score, preoperative hypertension, patent ductus arteriosus, and coarctation of the aorta were risk factors for postoperative hypertension, whereas transposition of the great arteries grouped with pulmonary atresia, pulmonary stenosis, and total anomalous pulmonary venous connection was a protective factor. The ventricular septal defect was a risk factor for postoperative hypertension but not for hypertension at discharge.Conclusions The incidence of postoperative systemic arterial hypertension is high in infants after cardiac surgery. The prevalence of hypertension decreased at discharge. Prospective long-term follow-up studies are needed to delineate the natural history of hypertension in high-risk children.